ไอ เอ็ม ซี คืออะไร - ฉวีลักษณ์ บุณยกาญจน (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Today, many libraries have begun the tradition into instructional media center or instructional materials centers (IMC) in order to provide more knowledge and experience for the customer. What is an IMC? It might be defined as a collection of print and nonprint materials and equipment so selected, arranged, located and staffed as to serve the needs of customer and to further the purpose of the schools, colleges and universities. The instructional materials (media) center (IMC) concept came into existence in America early at the turn of the 20th century as an extension of the library response to the need of individual and new method of teaching. Within a period of 35 years of development, its mission proved to be a good kind of library system which began as an idea to combine printed and nonprinted materials and was called an IMC.